Identifikasi Jenis Makroalga di Perairan Kampung Dormena Distrik Depapre Papua - Apriani Herni Rophi; Leonardo Elisa Aisoi; Edoward Krisson Raunsay; David R. Jesajas (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
potential if managed well. The Depapre coastal area is famous for its marine tourism. The sea water is still clean and clear, beautiful coral reef cover and the charm of seagrass beds with various types of fish that live around them are what attract tourists to visit this area. However, aquatic ecosystems, especially macroalgae, are under threat of degradation. The aim of this research is to identify types of macroalgae as initial data for monitoring and consideration in efforts to process biological resources, especially the composition and distribution of macroalgae.The method used is the roaming method (road sampling), the population of this study is various types of macroalgae found in Dormena coastal waters, while the research sample is all types of macroalgae found in the roaming area. The data obtained was processed qualitatively using a macroalgae identification key book. The results of research in the waters of Doromena village, identified 9 species of macroalgae, namely Chaetomorpha spiralis Okamura (Chorophyta), Halimeda macroloba Decaisne (Chorophyta), Phadina australis Hauck (Phaeophyta), Sargassum binderi (Phaeophyta), Sargassum cristaefolium C. Agardh 1820 (Phaeophyta), Turbinaria conoides (J. Agardh) Kützing 1860 (Phaeophyta), Chondrus crispus Stackh (Rhodophyta), Corallina officinalis Linnaeus 1758 (Rhodophyta), and Gelidium sp. J. V. Lamouroux 1813 (Rhodophyta).